Review of Data Collection Methods in Academic Research - Sanju Sharma (AG Volumes, 2025)
This review analyses the data collection techniques in scholarly research, and it is quite significant in assuring the validity, reliability, and credibility of the research findings. It talks about the data collection classification in the primary and secondary methods and also looks at quantitative, qualitative and mixed methods of data collection applied in various fields. Conventional methods like surveys, interviews, observations, and experiments are considered and modern digital methods are analyzed like online surveys, big data analytics, social media data and sensor-based systems. Informed consent, confidentiality, data security, and responsible use of AI are also highlighted as ethical considerations in the review, which also highlights that the collection of data by the methodologically sound and ethically sound data collection methods is needed.